Using the theory of planned behavior to assess participation in congregate meal programs - Lee, Kuei-I (Kansas State University, 2009)
Congregate meal programs under Older Americans Act Title IIIC provide hot meals for individuals 65 and older in a community setting during lunch time. The program focuses on preventing the problems associated with malnutrition and social isolation. From 1980 to 2002, the number of congregate meals served decreased by 18% while home-delivered meals increased almost 290%. To further understand reasons for declining program participation factors that impact participation were examined. The Theory of Planned Behavior (TPB) was used in this study to explain participation intention of community-dwelling elderly who lived in the Kansas North Central-Flint Hill region. A two-phased elicitation study including: 1) focus groups and 2) salient beliefs study was administered to uncover participation beliefs and identify and clarify salient belief items. Based on the results of an elicitation study and a literature review, a valid questionnaire was developed. Data were collected at a senior fair, senior centers, senior living facilities, senior exercise classes, and a monthly meeting of retired seniors yielding a total of 238 samples. Descriptive statistical analysis was used to summarize the respondent’s demographic characteristics. A two-step modeling approach including confirmatory factor analysis and structural equation modeling was performed to assess measurement model fit and checked causal relationships between factors. Five advantages that respondents believe influence participation include: convenience, social interaction, low-price, nutritious and balanced meals, and less waste. Family members, friends, neighbors, cooks at the meal site, and heath professionals were important referents who affected seniors’ program participation intention. The salient facilitators of program participation were activities at senior centers, the availability of transportation, the inclusive culture of senior centers, the lack of motivation and ability to cook, and poor weather. Results show the data fits the TPB moderately well: all predictor variables (attitude, subjective norm, perceived behavior control (PBC), and past behavior) had a significant positive effect on participation intention. Among the four factors, PBC had the greatest predictive power on intention. Attitude had the least impact on participation intention. Seniors provide thoughtful and insightful opinions about meal program. Results suggest program provider should focus on remove participation barriers and implement effective strategies to increase congregate meal program participation. The ultimate goal is to encourage the elderly to participate, improving their nutritional intake and thus, their quality of life.
Keywords: Theory of Planned Behavior; Congregate Meal Program; Gerontology (0351)